The Effect of Mind and Intelligence Games on University Students’ Perceived Stress and Psychological Well-Being Level - AKÇA, Coşkun; ÖZEL, Yasemin (Journal of Computer and Education Research, 2023)
This study aims to examine whether mind and intelligence games that support cognitive, social, and emotional skills have an effect on university students' perceived stress and psychological well-being levels. The population of the study consists of students actively studying at Kastamonu University Tosya Vocational School in the 2021-2022 academic year. Two groups of students were included in the study. While one of the groups had mind and intelligence game activities, the other group did not have these activities. The obtained data were analyzed using the statistical package program. As a result of the analysis, it was concluded that the psychological well-being levels of those who participated in the mind and intelligence game workshops were significantly higher in the positive direction and the perceived stress level was significantly lower in the negative direction compared to those who did not participate. According to the results of the research, it can be said that mind and intelligence games are an important educational tool used to support the psychosocial development of students and individuals and reduce stress.
Keywords: Alan Eğitimleri; Mind and intelligence games; perceived stress; psychological well-being; Other Fields of Education; 4. Education; 3. Good health